Nutrition transition in Vietnam: Changing food supply, food prices, household expenditure, diet and nutrition outcomes - Harris, Jody; Nguyen, Phuong Hong; Tran, Lan Mai; Huynh, Phuong (Springer, 2020)
While literature has noted the presence of a nutrition transition in terms of changing nutrition outcomes in Vietnam, very limited evidence linking changes in upstream food system factors to downstream diet and nutrition changes exists. Combining available data from different sources and analyzing it through a conceptual food systems framework, our study examines different pathways of nutrition transition through food supply, food prices, household food expenditures, diets, and nutrition outcomes in Vietnam. Our findings show that while Vietnam is at the start of its nutrition transition, change is happening rapidly. Undernutrition is falling, obesity is rising, and nutrition-related chronic diseases account for a significant burden of diseases and death. In terms of changes in healthful foods, the supply of vegetables and fruits is plentiful, and expenditure on vegetables remains consistent and small. Notably however, vegetable consumption has dropped, and increasing meat and milk consumption have been double-edged swords for nutrition. In terms of foods associated with the negative sides of the nutrition transition, the availability of sweets and sweetened beverages has risen in recent years, with oils and fats rising less. The expenditure share on food eaten away from home, in many contexts a marker for less healthful diets, has increased over time. While these changes are typical of a nutrition transition, Vietnam is also somewhat of an outlier in some respects: wet markets and daily fresh food purchases continue to dominate food purchasing behaviour, and food eaten away from home means a different thing in a country renowned for its diverse and healthy street food and roadside restaurant culture. While this study brings together important data on the food system drivers of a nutrition transition in Vietnam, it cannot link each of these issues into a standard statistical model of change due to data gaps at different levels, calling for data collection improvement in future diet and food systems research. Vietnamese health policy explicitly acknowledges nutrition transition issues, with targets for obesity reduction. This work on the food system drivers of the nutrition transition points to the need to further adapt policy in other sectors beyond health, however. At the same time as making nutrient-rich foods more accessible, nutrient-poor or ultra-processed foods need to be made less accessible and desirable if additional income is to contribute to a healthy diet in limiting Vietnam’s emerging nutrition transition.